Governança na comunidade pesqueira da Reserva Extrativista Marinha (RESEX) Prainha do Canto Verde: subsídios para incentivos socioeconômicos - Bonilla, Diana Alexandra Tovar (2019)
Market-based responses to address common-pool resource management issues have grown in the theory and practice of recent literature as the increase on research focused on Payments for Environmental Services (PES) suggests (Engel et al., 2008). However, few results and numerous critics call into question its efficacy (Muradian et al., 2010). As an alternative, since the 1980s the Ostrom (1990) studies in Socio-Ecological Systems (SES), found that collective action could guarantee a sustainable management of common-pool resources. The Marine Extractive Reserve (RESEX for its abbreviation in Portuguese) Prainha do Canto Verde (Ceará, Brazil) is an example of common governance and community resistance in the struggle to maintain the territory against major threats such as predatory fishing and largescale tourism. The RESEX is characterized by the presence of 359 households, it is composed by a morphological unit of a coastal plain landscape with a complex and dynamic environment geosystem with high levels of instability. The traditional local fishing is its main activity and hold Bolsa Verde and Seguro Defeso programs that have been considered as PES schemes under the public administration model (SIMÕES; ANDRADE, 2013; BEGOSSI et. al., 2011). This research seeks to analyze the fishing resources governance of the RESEX Prainha do Canto Verde by observing the concurrence between state, community and the government programs Bolsa Verde and Seguro Defeso. Following the SES methodological framework developed by Ostrom (2007; Poteete et al., 2012) semi-structured interviews were conducted with key participants from the community and key institutions, and 39 households were surveyed, the fieldwork also included participant observation and workshops with the local community for mapping ecosystem services. We preliminary finding a greater influence from the community rules over the government incentives to ensure the sustainability of the fishing resources.